A Comparative Investigation of Prescriptive Ophthalmic Lens Parameters with Iranian National Standards - Mohammad Ghassemi Broumand; Hassan Ghasemi; Saeed Rahmani; Seyed Mehdi Tabatabaeei; Mohammad Reza Nazari; Mohsen akhgary; Pourya Ghasemi Bruomand (Shahid Beheshti University of Medical Sciences, 2013)
Background and Aim: Wearing spectacles is the most common procedure for correction of refractive error and because of its close relationship with eye; the standards of frame & lens of glasses play a very important role in preventing vision problems. The purpose of this study was to compare spherical & cylindrical power and prismatic effect of plastic ophthalmic lenses with Iranian national standards.Material & Method: In this Cross sectional-Comparative study 48 plastic ophthalmic single vision lenses were inspected & compared with relative national standards i.e.: ISIRI 8715-1:1385.Results: The spherical power factor with instruments set as step 0.01, all the cases(-1.00,-3.00,-6.00) were in tolerance with limits of the standards (±0.12 D) .The instrument was set for 0.01 step for cylindrical power, at -6.00 D 100% of lenses had no cylindrical power. At -3.00 & -1.00 D about 99% were in tolerance with the standards (±0.09 D).The effect of horizontal & vertical prism, at the power of -6.00 all lenses show prismatic effect but 99% were in tolerance with the standards (±0.85D). At the power of -3.00 & -1.00 D, prismatic effect of lenses were in tolerance with relative standards (±0.55, ±0.35), respectively. Conclusion: All single vision were collected from famous companies showed the quality of passing all factors of tests & gained Iranian national standards i.e.: ISIRI 8715-1:1385.